Miopia pada Anak dan Faktor Risikonya Selama Pandemi COVID-19: Sebuah Tinjauan Sistematis - Tan, Sabrina; Yulia, Dian Estu (Fakultas Kedokteran Universitas Trisakti, 2024)
Myopia or near-sightedness is the most common ophthalmologic disorder in the world. Myopia prevalence has significantly increased over the last decade, especially in the pediatric population. During the COVID-19 pandemic, governments worldwide implemented home quarantine and school closures to contain and mitigate the virus’s spread. This resulted in increased screen time, more time doing near-work activities, and decreased time spent outdoors. This study was to compare myopia progression in children before and during the COVID-19 pandemic and examine pandemic-related lifestyle risk factors for myopia progression. Methods of this study were A comprehensive search of Ovid MEDLINE and PubMed for potential articles was conducted following the PRISMA 2020 guidelines. The data extracted from each included studies included epidemiologic data on myopia in children, changes in spherical equivalent (SE), and the amount of outdoor activity, screen time, and near work before and during the COVID-19 pandemic home quarantine. This review included six studies, comprising two retrospective cohort studies, three prospective cohort studies, and one cross-sectional study. Epidemiological data showed increased pediatric myopia cases and a greater SE difference during the COVID-19 pandemic. During the pandemic, it was reported that children spent more time on screens, engaging in near-work activities, and less time outdoors. Multiple logistic regression analyses consistently showed increased screen time as a significant risk factor for myopia in children during the pandemic, while outdoor time and time spent doing near-work activities were not statistically significant. Conclusion of this study where Myopia progression in children was more rapid during the COVID-19 pandemic, with increased screen time identified as a risk factor. More research is needed to further investigate other pandemic-related risk factors for myopia in children.